Risk Management Implementation Analysis As Realizing Good Corporate Governance In Retail Companies In Makassar - Siti Fatima; Muhammad Ali (Jurnal Mirai Management, 2023)
This study aims to determine the effect of risk management on achieving good corporate governance in PT. Hero Supermarket Tbk. The population in this study were all HERO supermarket employees in Makassar city, especially Jl. Sultan Alauddin, a total of 33 years using a purposeful sampling method. The data analysis technology used is SWOT analysis technology, by identifying strengths, weaknesses, threats especially the risks faced, the risk identification process was developed from 5W1H (what, where, when, who, why & how) through the brainstorming of Heroes of management and staff. The results of the study show that there is an influence of 67.7%, where the result has a positive and strong effect, indicating that the relationship between the two variables is in line with the theory put forward by experts and the application of risk management has an impact on realization. of GCG, the implementation of risk management plays an important role in ensuring the realization of GCG principles towards the environment of PT Hero Supermarket Tbk. Keywords: Risk Management, Good Corporate Governance, Retail Companies